ACTUALIZATION OF TEACHERS' STRATEGIES IN OVERCOMING BULLYING AT MI HADRUL ULUM CISALAK - Opi Ropikoh; Devi Vionitta Wibowo (Universitas Pendidikan Indonesia, 2023)
This study aims to: (1) describe the teacher's strategy in overcoming bullying behavior at MI Hadrul Ulum Cisalak (2) analyze the teacher's obstacles in overcoming bullying behavior atMIHadrul Ulum Cisalak. To answer the problems that occur in this study, the research used BF Skinner's Behaviorism Theory. The type of research used is a qualitative approach with a case study research method. The research location is at Madarasah Ibtidaiya (MI) Cisalak which is located at Cisalak Village. In data collection techniques using observation, interviews and documentation, while determining informants using purposive sampling techniques. Whereas in data analysis techniques using data collection techniques, data presentation, drawing conclusions, and data validity. The results of this study indicate that the teacher' strategy in overcoming bullying behavior at MI Hadrul Ulum Cisalak is: (1) knowing the root causes of bullying, (2) giving punishment (punishment), (3) making study groups, (4) giving advice to students who engage in bullying behavior and other students, (5) provide several services from BK to students who are victims of bullying and bullies, (6) provide rewards, (7) provide